Russia has Spread its Wings. Phenomenology of our Era Global Systematic Contradiction Development - V. I. Karpunin; T. S. Novashina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article reveals specific features of the present day stage in the global systematic contradiction ‘creditors – debtors’ development. The origin of its critical stage was depicted in the context of form variety in the total hybrid, informational war that was projected well in advance, thoroughly worked-out and unleashed in a mass way against Russia by overseas and over-oceans Anglo-Saxon political elites. Technologies of the present day informational wars were studied and tools of cynical manipulation of public opinion of people in their own countries used to obtain a mass support of any decisions made by their governments were described. The massive information flow is meant to form a smoke-screen, which could hide real goals and intentions of architects of global domination. Deliberately formulated lies aim at discrediting a previously chosen object in eyes of the global public. This object is a nominated institutional enemy. This object forms a barrier due to its natural being and it is absolutely unacceptable for a new idea, i.e. global dominating exalted by British political elite to the strategic imperative of this implicit, pressing demand. Strategic imperative has a direct meaning, it is an official doctrine presented in a solemn, high-society atmosphere by the head of the Ministry of Foreign Affairs of Great Britain in the London City. The implicit demand, forming the essence of strategic imperative arose, grew and was promoted by all possible ways. This demand makes today the essence of Anglo-Saxon elites’ interests, the essence of any form of overthrowing the enemy in the process of developing the global systematic social-economic antagonism ‘creditors-debtors’. Today contradiction of interests of social groups forming poles of this antagonism passed over to the stage of global systematic antagonism of our era and has reached its climax. To attain the longed-for goal of strategic imperative for all of us London is going to stick to a new approach in international relations, which will be based on three spheres: military force, economic security and more advanced global alliances. Strategy of British political elite was defined and declared in public. An open, unprecedented by its aims and attracted resources challenge was thrown down to institutional enemies. Russia has accepted the challenge. Today Russia is facing numerous most serious problems that must be settled without any doubts.